PROCESSOS QUÍMICOS DE GÊNESE DE DEPÓSITOS DE ARGILOMINERAIS A PARTIR DE ROCHAS VULCÂNICAS DA FORMAÇÃO CAMPO ALEGRE (SC) - Biondi, J. C.; Vanzela, G. A.; Bartoszeck, M. K. (Geochimica Brasiliensis, 2011)